MEDIA DEVELOPMENT OF COMIC WORKSHOP FOR MATHEMATICS LEARNING STUDENTS FOR CLASS V SD - Rizka Nanda Prasetyo; Ervika Dewi; Maria Ulfa Yudha Julistiana (Universitas Islam Balitar, 2021)
The research development was carried out in order to overcome the problems of students who felt difficulties in Mathematics in grade V SD. The development of this research is so that students are enthusiastic about learning mathematics and change the mindset of elementary school students that learning mathematics is not difficult and even tends to be fun. This research was conducted by Research and Development. The initial process of making pictorial story material and comic illustrations was then validated by a team of media experts, linguists and material experts. Continue to be tested in small groups in order to see the level of readability and student response to a learning medium for students and teachers, so that it can be concluded that the comic strip media for learning mathematics can be used as a medium for learning mathematics in grade V SD. The results of the research on Mathematics Learning Comic LKS for grade V SD have been developed according to the stages according to Sugiyono which are limited to seven stages. At the validation stage, it shows that the results of the material expert validation obtained a percentage score of 80.6%, including the feasible criteria. The results of the linguist validation obtained a percentage score of 83.3%, including the feasible criteria. The results of the media expert validation obtained a percentage score of 82%, including the feasible criteria. In the readability test, students towards the media got a score of 85.6% and in the response test students got a score of 91%, so it can be concluded that the media is very feasible.